Computer Simulation of the Dynamic Operating Modes of Thermoelectric Device for Cryodestruction - Anatychuk, L. I.; Vikhor, L. M.; Kobylianskyi, R. R.; Kadeniuk, T. Ya. (Physics and Chemistry of Solid State, 2017)
This paper presents the results of computer simulation of optimal dynamic modes of thermoelectric device for cryodestruction. The optimal time function for controlling the supply current to thermoelectric micromodule in a device for cryodestruction is determined, which ensures given cyclic temperature effect on the local area of human body.